The influence of the expanded Global Gag Rule on Malawi’s sexual and reproductive health and rights landscape: a qualitative study - Bergen Cooper; Roger Rochat; Aishwarya Iyer; Samantha M Luffy; Anna Newton-Levinson; Honora Cargile; Savannah Miller; Anisha Sheth; Maggie Switzer; Allison Wynne (BMJ Global Health, 2025)
Introduction The Global Gag Rule (GGR) prohibits non-governmental organisations receiving US international family planning funding from using these funds to provide or refer for abortion services or advocate for abortion law liberalisation. In 2017, President Trump renamed the policy Protecting Life in Global Health Assistance (PLGHA) and expanded it to all US global health assistance funding. On 28 January 2021, President Biden revoked PLGHA. Limited research explores the expanded GGR’s influence when revoked in countries dependent on US global health assistance. We examined how PLGHA influenced the sexual and reproductive health and rights (SRHR) landscape of Malawi during its enforcement and since its revocation by President Biden in January 2021.Methods We conducted semi-structured qualitative interviews between July and August 2021 with 17 current and past recipients of US global health assistance and civil society organisations working in SRHR in Malawi.Results While PLGHA was in effect, participants observed the stalling of a liberalised abortion bill in Parliament, enhancement of anti-abortion attitudes and hindrance of national sovereignty in Malawi. In some cases, participants reported that over-implementation of the policy restricted legal access to post-abortion and contraceptive care. The Biden administration’s revocation of PLGHA seemed to exemplify support of SRHR globally but did not reverse anti-abortion sentiment emboldened by prior enforcement of the policy. The threat of PLGHA being reinstated by a future US president was associated with hesitation among participants to invest in public health programmes and advocacy efforts.Conclusion Participants felt that PLGHA’s enforcement was associated with impaired abortion law reform, prevented organisations from providing safe post-abortion care and reinforced abortion stigma in Malawi. Participants felt these impacts endured even after the policy’s revocation in January 2021. A permanent repeal of the GGR would allow organisations and the Malawi government to fully invest in public health interventions promoting SRHR.